Peningkatan Pengetahuan Masyarakat tentang Mitos dan Fakta Diabetes Melitus serta Diet Seimbang Penderita Diabetes Melitus - Sunarti Sunarti; Rochana Ruliyandari; Emanuel Depa Chrisnandy; Maharani Nusara Ardhi; Candra Puspitasari; Renni Renni; Arihni Arihatal Jannah; Noernahar Septisari Usman; Veronica Sukardi Jaya; Ratnawati Ratnawati; Jumaiah Jumaiah (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2023)
Community service activities are a forum for sharing information to increase public knowledge. This community service is conducted online through seminars using the Zoom meeting application with the theme "Myths and Facts of Diabetes Mellitus and a Balanced Diet for Diabetes Mellitus Patients". This service aims to inform the public about the myths and facts about diabetes mellitus and increase public knowledge regarding proper prevention and control. The participants consisted of health cadres in Sangatta, East Kalimantan, and the general public, totaling 47 people. Material delivery was carried out using lecture methods with PowerPoint presentations, discussion, and questions and answers. The activity results were evaluated using a quasi-experimental design by comparing the pre-test and post-test results of the participants. The data is not normally distributed, so the difference test used is the Wilcoxon test. This community service increased participant knowledge with a p-value of 0.000 (p<0.05) and increased the average participant knowledge score from 80 ± 16.923 to 90 ± 10.301. This community service activity concludes that the activity can increase community knowledge related to proper prevention and control of diabetes mellitus.